Prospects for the Use of Martensites in the Manufacture of Adaptive Anti-Slipping Spikes: Advanced Study - Voiku, I. P.; Sergeeva, T. V.; Strikunov, A. V. (New Approaches in Engineering Research Vol. 5, 2021)
The article substantiates the relevance of the development of an innovative device, namely an adaptive anti-slipping spike, and the prospects for the use of martensites in its manufacture. The device belongs to the automotive industry, specifically to the anti-slipping spikes. Tire treads of vehicles are equipped with these spikes to increase their adhesion to the roadway. The use of traditional anti-slipping spikes does not allow solving two problems at the same time: to ensure maximum adhesion of the vehicle’s wheel to the road surface and to minimize the destructive effect of anti-slipping spikes on the road surface. These tasks are solved by the fact that the proposed device is made according to the shape and size of traditional anti-slipping spikes but contains a retractable pin. The pin can be operated either by the substances with a negative coefficient of thermal expansion or martensitic materials. The article describes the prospects and features of their use.